2015
DOI: 10.1016/j.pocean.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling two alternative mechanisms behind bi-decadal variability in the North Atlantic

Abstract: International audienceUnderstanding the preferential timescales of variability in the North Atlantic, usually associated with the Atlantic meridional overturning circulation (AMOC), is essential for the prospects for decadal prediction. However, the wide variety of mechanisms proposed from the analysis of climate simulations, potentially dependent on the models themselves, has stimulated the debate of which processes take place in reality. One mechanism receiving increasing attention, identified both in ideali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(79 citation statements)
references
References 57 publications
10
67
2
Order By: Relevance
“…However, using observational data, Frankcombe et al (2008) observed the signature of large-scale SST and Sea Surface Height anomalies, propagating westward across the North Atlantic ocean. In addition, Sévellec and Fedorov (2013) show that, in a 2° global configuration of the OPA (Océan PArallélisé) model with realistic topography, the least damped mode of variability of the tangent adjoint linear model remains a potential candidate to explain the MOC multidecadal variability (Ortega et al 2015). This mode is characterized by large-scale temperature anomalies that propagate westward across the subpolar gyre, associated with long baroclinic Rossby waves .…”
Section: Summary and Discussionmentioning
confidence: 96%
“…However, using observational data, Frankcombe et al (2008) observed the signature of large-scale SST and Sea Surface Height anomalies, propagating westward across the North Atlantic ocean. In addition, Sévellec and Fedorov (2013) show that, in a 2° global configuration of the OPA (Océan PArallélisé) model with realistic topography, the least damped mode of variability of the tangent adjoint linear model remains a potential candidate to explain the MOC multidecadal variability (Ortega et al 2015). This mode is characterized by large-scale temperature anomalies that propagate westward across the subpolar gyre, associated with long baroclinic Rossby waves .…”
Section: Summary and Discussionmentioning
confidence: 96%
“…1a (colors) by its first empirical orthogonal function (EOF). The first mode of variability is an overturning cell with a large vertical extension reaching down to 4000 m. The 20-yr periodicity is primarily related to the westward propagation of subsurface density anomalies in the subpolar basin, referred to as the subsurface basin mode in Ortega et al (2015). Such variability has been identified in observations (Frankcombe et al 2008) and in idealized ocean models (Colin de Verdière and Huck 1999;Jamet et al 2016).…”
Section: Amoc Variabilitymentioning
confidence: 95%
“…1b, the AMOC is followed 8 yr later by a surface warming of the subpolar basin, consistent with the increased northward heat transport from the subtropical Atlantic to the subpolar basin. Ortega et al (2015) argued that this warming is associated with negative density and anticyclonic ocean circulation anomalies in the eastern subpolar basin between 300 and 1000 m, which follow the AMOC by 5 yr. This leads to a reduction of the oceanic northward heat transport into the Nordic seas, which also occurs about 5 yr after an intensification of the AMOC (Fig.…”
Section: Amoc Variabilitymentioning
confidence: 99%
“…This is the same model version used in previous perfect model studies focused both on surface nudging techniques for ocean initialisation (Servonnat et al 2015) and potential predictability of the AMOC (Persechino et al 2013), and has been extensively used in other studies analysing mechanisms of natural decadal variability in the North Atlantic (Escudier et al 2013;Ortega et al 2015), as well as evaluating historical decadal prediction skill in the ocean through surface nudging Mignot et al 2015). Using IPSL-CM5A-LR thus allows us to benefit from this in-depth expertise of the model, and also from its relatively cheap computational cost, ideal to run several sets of ensemble experiments.…”
Section: Model Configurationmentioning
confidence: 99%
“…1). This corresponds to the latitude where the full AMOC streamfunction and the northward thermal-wind transport reach their climatological maximum in the model (Ortega et al 2015). Since our interest lies in the thermohaline-driven component of the AMOC, the Ekman transport signal is removed from the MOI-48N index.…”
Section: Performance Of the Standard Nudging Techniquesmentioning
confidence: 99%